Effects of cholinium-based ionic liquids on Aspergillus niger lipase: Stabilizers or inhibitors - Nascimento, Paloma A. M. [UNESP]; Picheli, Flávio P. [UNESP]; Lopes, André M. [UNESP]; Pereira, Jorge F. B. [UNESP]; Santos-Ebinuma, Valéria C. [UNESP] (Wiley, 2019)
Lipases are well-known biocatalysts used in several industrial processes/applications. Thus, as with other enzymes, changes in their surrounding environment and/or their thermodynamic parameters can induce structural changes that can increase, decrease, or even inhibit their catalytic activity. The use of ionic compounds as solvents or additives is a common approach for adjusting reaction conditions and, consequently, for controlling the biocatalytic activity of enzymes. Herein, to elucidate the effects of ionic compounds on the structure of lipase, the stability and enzymatic activity of lipase from Aspergillus niger in aqueous solutions (at 0.05, 0.10, 0.50, and 1.00 M) of six cholinium-based ionic liquids (cholinium chloride [Ch]Cl; cholinium acetate ([Ch][Ac]); cholinium propanoate ([Ch][Prop]); cholinium butanoate ([Ch][But]); cholinium pentanoate ([Ch][Pent]); and cholinium hexanoate ([Ch][Hex])) were evaluated over 24 hr. The enzymatic activity of lipase was maintained or enhanced in the lower concentrations of all the [Ch]+-ILs (below 0.1 M). [Ch][Ac] maintained the biocatalytic behavior of lipase, independent of the IL concentration and incubation time. However, above 0.1 M, [Ch][Pent] and [Ch][Hex] caused complete inhibition of the catalytic activity of the enzyme, demonstrating that the increase in the anionic alkyl chain length strongly affected the conformation of the lipase. The hydrophobicity and concentration of the [Ch]+-ILs play an important role in the enzyme activity, and these parameters can be controlled by adjusting the anionic alkyl chain length. The inhibitory effects of [Ch][Pent] and [Ch][Hex] may be of great interest to the pharmaceutical industry to induce pharmacological inhibition of gastric and pancreatic lipases.
Keywords: choline; enzymatic activity; inhibition; ionic liquid; lipase interaction; stability